Molecular characteristics and cancer immunity of LRP1B and its relationship with the Hedgehog signaling pathway in colorectal cancer - Liu, Yuan; Zhong, Yang; Sang, Yaodong; Zhu, Siqiang; Xu, Kang; Zhu, Xingyu; Cui, Xiaoling; Liu, Xinyu; Wang, Xiaohan; Chen, Hao; Jing, Changqing; Chong, Wei; et al. (Frontiers in Immunology, 2025)
BackgroundColorectal cancer (CRC) is a malignant tumor of the digestive tract that significantly impacts human health. LDL receptor-related protein 1B (LRP1B) may play a crucial role in tumorigenesis and disease progression.MethodsWe performed a comparative analysis of differential gene expression, mutation patterns, drug sensitivity, and cellular phenotypes across different subgroups with varying LRP1B expression levels. Cellular and molecular experiments were conducted to validate our findings.ResultsOur analysis implicated LRP1B as a tumor suppressor gene. Experimental results confirmed that LRP1B expression was reduced in CRC and its knockdown was associated with poor prognosis. Molecular mechanism studies revealed that LRP1B negatively regulated the Hedgehog (Hh) signaling pathway, influencing cell cycle and apoptosis processes. Single-cell analysis showed significant differences in the infiltration of T cells, B cells, epithelial cells, and myeloid cells between high and low LRP1B expression groups. Immune cell infiltration and drug sensitivity analyses demonstrated that LRP1B plays a crucial role in immunotherapy and targeted therapy, suggesting that restoring LRP1B function could be a promising treatment strategy for CRC.ConclusionOur results indicate that LRP1B may function as a tumor suppressor factor in CRC, playing a significant role in mutation, therapy, and immune infiltration. Knockdown of LRP1B activates the Hh pathway in tumor cells, leading to the inhibition of several malignant biological behaviors.